Effects of meat and poultry recalls on firms' stock prices - Pozo, Veronica F. (Kansas State University, 2014)
Food recalls have been an issue of great concern in the food industry. Stakeholder responses to food safety scares can cause significant economic losses for food firms. Assessing the overall impact that may result from a food recall requires a thorough understanding of the costs incurred by firms. However, quantifying these costs is daunting if not impossible. A direct measurement of a firm’s total costs and losses of revenue associated with a food recall requires firm-level data that is not available. The method utilized in this study overcomes this severe limitation. Using an event study, the impact of meat and poultry recalls is quantified by analyzing price reactions in financial markets, where it is expected that stock prices would reflect the overall economic impact of a recall. A unique contribution of this study is evaluating whether recall and firm specific characteristics are economic drivers of the magnitude of impact of meat and poultry recalls on stock prices. Results indicate that on average shareholders’ wealth is reduced by 1.15% within 5 days after a firm is implicated in a recall involving serious food safety hazards. However, when recalls involve less severe hazards, stock markets do not react negatively. Also, reductions in company valuations return to pre-recall levels after day 20. Firm size, firm’s experience, media information and recall size are drivers of the economic impact of meat and poultry recalls. That is, firms recalling a larger amount of product perceive greater reductions in company valuations. Additionally, recalls issued by larger firms are less likely to present negative effects on stock prices, compared to smaller firms. Moreover, firms that have recently issued a recall are less harmed by a new recall compared to those firms issuing a recall for first time. Thus, suggesting that investors take into consideration the past performance of a company when dealing with food recalls. Furthermore, media information has a negative impact on shareholder’s wealth. Findings from this study provide essential information to the meat industry. In particular, understanding the likely impact of such “black swan” events is critical for firm’s investing in food safety technologies and protocols.
Keywords: Food safety; Food recalls; Stock prices; Abnormal returns; Event study; Economics, Agricultural (0503)